A computational approach to design putative potential siRNAs for silencing the nucleoprotein and surface glycoprotein gene of MARV - Suraiya, Tasnia Iffat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.